Peningkatan Kesehatan Masyarakat melalui Pemberdayaan Wanita dalam Pemanfaatan Lahan Pekarangan dengan Tanaman Obat Keluarga (TOGA) - Suaibatul Aslamiah; Ise Afitah; Mariaty Mariaty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This service activity carried out in the village Langkai slender Pahandut districts in community groups Perumahaan Borneo. The selection of this location because in general, the women in the village built is not working, so had plenty of time to become empowered and more rapidly in accepting technology. This activity aims to help mothers and young women to improve family health by reducing expenses in medicine and improve the utilization of the yard with a plant that functions as medicinal plants. Application activity is the introduction of several types of plants that serve as a remedy. In some women there who are already active in exploiting the yard, then the implementation of the activities is the enrichment kind of TOGA and function. The method used is planting demonstration counseling and mentoring. Activity results showed that women in the target group in two groups RT Borneo and Candra Buana group has formed a TOGA garden in her yard. Evaluation of this activity is a very good response, each group in two households has a garden TOGA, so the evaluation is the increased utilization of the yard seventy-five percent.